2012
DOI: 10.1128/aem.07959-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution of the Complete Clostridium thermocellum Cellulosome and Synergistic Activity on Crystalline Cellulose

Abstract: ABSTRACTArtificial cellulase complexes active on crystalline cellulose were reconstitutedin vitrofrom a native mix of cellulosomal enzymes and CipA scaffoldin. Enzymes containing dockerin modules for binding to the corresponding cohesin modules were prepared from culture supernatants of aC. thermocellum cipAmutant. They were reassociated to cellulosomes via dockerin-cohesin interaction. Recombinantly produced mini-CipA prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 44 publications
6
60
0
Order By: Relevance
“…Krauss et al (24) reported that the addition of scaffoldin to the scaffoldin-disrupted C. thermocellum culture supernatant increased the cellulase activity only when Avicel was used as a substrate, whereas it did not differ greatly when PASC or soluble cellulose was used, which suggests an exclusive proximity effect on Avicel. From this report, we expected that the arming yeast would show an even greater proximity effect on Avicel and we measured the Avicel-degrading activity of MIX-yeast and ALLyeast (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krauss et al (24) reported that the addition of scaffoldin to the scaffoldin-disrupted C. thermocellum culture supernatant increased the cellulase activity only when Avicel was used as a substrate, whereas it did not differ greatly when PASC or soluble cellulose was used, which suggests an exclusive proximity effect on Avicel. From this report, we expected that the arming yeast would show an even greater proximity effect on Avicel and we measured the Avicel-degrading activity of MIX-yeast and ALLyeast (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The cell pellet was resuspended using 500 l of a 100 mM citrate buffer and incubated in a heat block at 50°C for 1 h, after which 500 l of 2% PASC was added to start the reaction (which was performed at 50°C). Reaction samples were withdrawn at 6, 12, 24, and 48 h of incubation in the case of OD10 yeast cells and at 24,48,84, and 120 h of incubation in the case of OD0.1 yeast cells, and then the supernatants were mixed with 3,5-dinitrosalicylic acid (DNS) solution (NaOH, 16 g/liter; potassium sodium tartrate, 300 g/liter; DNS, 5 g/liter) in a 1:2 ratio to quantify the reduced ends of the degraded products. The mixed solutions were incubated at 100°C for 5 min, and after cooling them to room temperature, 200 l of each solution was used for measuring the A 530 using the Fluoroskan Ascent fluorometer and 96-well black plates.…”
Section: -Morpholinoethanesulfonic Acid (Mesmentioning
confidence: 99%
“…These deletion variants display two or three enzyme molecules (8,(11)(12)(13), whereas the number of cohesin modules in native cellulosomal scaffoldin proteins is typically between 6 and 11 (1). These minicellulosomes usually show significantly lower activity toward crystalline cellulose than do native cellulosomes (8,12,14). Thus, elucidating the mechanism responsible for the high activity for crystalline cellulose exhibited by native cellulosomes requires in vitro reconstitution of the cellulosome complexes from their large scaffoldin proteins.…”
mentioning
confidence: 99%
“…The cellulolytic activity of the in vitro-reconstituted cellulosome, comprising full-length CipA produced by recombinant E. coli cells and the protein mixture secreted from cipA-deficient C. thermocellum cells, has recently been investigated (14). The reconstituted cellulosome was assembled by assuming that the secreted protein mixture has an average molecular mass of 80 kDa.…”
mentioning
confidence: 99%
“…Localization of broad substrate range enzymes and their close proximity for efficient formation of enzyme-substrate complex are the significant factors for increasing the efficiency of the cellulosomes. Cellulosomes are known to have better enzymatic activity as compared to free enzymes because of the close proximity of various cellulases which act synergistically (Blanchette et al 2012;Krauss et al 2012;You et al 2012a). However, the mechanism of protein assembly and organization of various catalytic enzymes in the cellulosomes is partially known (Wilson 2011).…”
Section: Cellulosomal Enzymesmentioning
confidence: 99%